Kusen Snacks Bakery system / Nur Hafizah Ahmad, Mariam Abd Malik and Nurul Syafika Roslan - Ahmad, Nur Hafizah; Abd Malik, Mariam; Roslan, Nurul Syafika (2012)
Information technology plays a vital role in the business professions nowadays. Web based system made business deals very easy. Kusen Snacks Bakery (KSB) system is a web based application, a solution for Kusen Snacks Bakery to record and keep data. We are providing a fast and efficient way of entering and storing data using database management system. There is an issue of manual filing of KSB consumed more spaces to recorded data, more time to find certain details. As a result, more office equipment is needed to keep all files and it is difficult for staffs to retrieve data. Furthermore, reporting requirement is getting more complex as number of orders is different each day and has been increasing as the business developed. The methodology that has been chosen is the agile methodology. It is the best choice because it helps teams respond to the unpredictability of building software or application web based through incremental and iterative work cadences. The emergence of this system can help the staff a lot in doing their work. Therefore, they can manage their work properly. The conclusion is that an easy-to-use interface and database has been created for KSB to achieve the initial objective of this project.